Development and initial testing of an active low-power, ferroelectric film-based bioaerosol sampler. Issue 12 (1st November 2022) - Grogan, Sydonia N. C. M.; Han, Taewon T.; Mainelis, Gediminas
Abstract: This article introduces REAS (Rutgers Electrostatic Active Sampler), a new active bioaerosol sampler using permanently polarized ferroelectric film (e.g., PVDF) to capture charge-carrying bioaerosol particles. While REAS operates on an electrostatic collection principle, due to its unique materials and design, it does not require external power to charge incoming particles or to create an electrostatic collection field. The sampler consists of a polarized film wound in a spiral configuration with oppositely polarized film sides positioned 2.25 mm apart. The film and its holder are inserted into a 3D-printed housing cylinder to connect to a pump. The device has an open channel design, creating virtually no pressure drop, which allows for longer sampling times on the same battery charge compared to filter samplers. When REAS was tested in different field environments, the physical collection efficiency ranged from 19 ± 2% in a laboratory environment at 1 L/min to 41 ± 0.1% in residence at 0.1 L/min. When REAS was used to capture culturable bacteria and fungi over a 24-hr period, the concentrations determined by REAS were not different from those determined by an Institute of Medicine sampler (IOM, SKC, Inc.). The concentrations determined by both samplers were lower than those measured by a SAS Super 180 Sampler (SAS, Bioscience International), except for outdoor fungi. However, the SAS was used as a grab sampler to avoid overloading or desiccating the plates, while both REAS and IOM continuously sampled for 24 hrs. Further studies will explore improvements to the REAS sample elution protocols. Copyright © 2022 American Association for Aerosol Research GRAPHICAL ABSTRACT: UF0001